PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATISiPESERTA DIDIK KELASiXI MIPA - Nasution, Anggi Fadillah (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical communication ability is one of the objectivesiof learning mathematis. However, in reality the mathematical communication skills of students in class XI MIPA SMAN 5 Padangsidimpuan are still low. One of the efforts that can be made to overcome this problem is by applying the Think Talk Write cooperative learning model. The purpose of this study was to find out whether the mathematical communication abilities of students who studied with the Think Talk Write cooperative learning model were better than those who learned with direct learningiin class XI MIPA students at SMAN 5 Padangsidimpuan. The typeiof reseach used is quasi-experimentaliresearch with a non-equivalent posttest only kontrol groupidesign. Theipopulation inithis study were all studentsiin class XI MIPA at SMAN 5 Padangsidimpuan for the 2022/2023 acadmic year. Samplesiwere taken using the Simple RandomiSampling technique. The instrument used is in theiform of a testiof mathematicalicommunication skills. Basedion the analysis of the test of matematical communication skills, P-value = 0.022 was obtained. Because the P-value iis less than α = 0.05, it meansithat there is influence from the application of the ThinkiTalk Writeicooperativeilearning model on students' mathematical communicationiskills. Keywords – ThinkiTalk Write, MathematicaliCommunication Ability